TEACHING IDEOLOGIES THROUGH DESIGN THE EXPERIENCE OF COLLECTIVE HOUSING DESIGN STUDIO AT THE FACULTY OF ARCHITECTURE OF OPORTO - Marco Ginoulhiac (2012)
The design studio teaching is the pedagogical space where ideological settings become action rules and material procedures. When the students start to design, they unconsciously are putting in action a theoretical framework they acquired during their studies as future architects and during their existence as human beings and citizens. In the Collective Housing Design Studio this relationship between an ideological framework and a built and inhabited reality represents its pedagogic and didactic basement. Indeed is required to the student to stress some theoretical notions in order to see how the architecture discipline can answer to the complexity of a social request. In other words the Collective Housing Design Studio is the place where, more than ever, teaching architecture became architectural education. At the Faculty of Architecture of Oporto, the course of "Projecto 3" is traditionally a Collective Housing Design Studio and represents, by his own professors and didactical processes, the heritage of a historical and almost unique experience between architects and ideological principles: the SAAL. After the Portuguese revolution of 25th April, 1974, a strong housing need caused the creation of the SAAL (Local Support Service Ambulatory). The SAAL was a kind of architectural task-forces that operated in deteriorated and low income urban areas to design low cost housing for local people. Many professors that taught (and still teach) at the FAUP were SAAL's members and had the opportunity to participate in the political, social and design processes. The heritage of this experience is still today present in the teaching method and ideology that support the Collective Housing Design Studio course and is visible through a continuous afford for a systematical approach to a large number of questions related to the housing design. The course program is built to take the student as close as possible to this exercise that starts in the world of ideas and ends in the concrete world.